2009
DOI: 10.1080/08039480802423014
|View full text |Cite
|
Sign up to set email alerts
|

Forensic psychiatric patients among immigrants in Denmark – Diagnoses and criminality

Abstract: The purpose of this study is to analyse a sample of immigrant forensic psychiatric patients and to compare them with Danish patients. Of the 326 forensic patients in Copenhagen, 111 were immigrants or descendants of immigrants. The sample was broken down according to area of origin, age, gender and ethnic status. The data have been analysed by Poisson regression with the background population as an offset variable. Of the patients of non-Danish ethnicity, a significantly higher ratio was diagnosed with schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Moving to a new country and culture is known to be a psychosocial stressor and risk factor for developing mental illness, also after trauma. This has also been found in other Nordic countries [45,46].…”
Section: Effects Of Migration and Integrationsupporting
confidence: 84%
“…Moving to a new country and culture is known to be a psychosocial stressor and risk factor for developing mental illness, also after trauma. This has also been found in other Nordic countries [45,46].…”
Section: Effects Of Migration and Integrationsupporting
confidence: 84%
“…A total of five studies received a high score on methodological quality (Bhui et al, 1998;Coid & Ullrich, 2011;Gabrielsen & Kramp, 2009;Gosden et al, 2006;Vinkers et al, 2013). Three of these studies found significant higher prevalence rates of psychotic disorders in BME detainees compared to non-BME detainees (Bhui et al, 1998;Gabrielsen & Kramp, 2009;Vinkers et al, 2013) whereas the other two could not find any significant ethnic variations regarding the prevalence rates of psychotic disorders (Coid & Ullrich, 2011;Gosden et al, 2006).…”
Section: High Quality Studiesmentioning
confidence: 99%
“…One difference between the high-quality studies with equivocal findings is the number of ethnic groups under study: high quality studies that found ethnic variations separated five (Bhui et al, 1998), seven (Gabrielsen & Kramp, 2009) and eight (Vinkers et al, 2013) different ethnic groups respectively, whereas both studies that did not, only investigated two ethnic groups (Coid & Ullrich, 2011;Gosden et al, 2006). These lower numbers of ethnic groups under study may have resulted from the fact that the latter two studies were not hypothesis driven when comparing ethnicity, but rather focused on psychotic prisoners in general.…”
Section: High Quality Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia was a factor in the occurrence of crimes involving violence but not a factor in non-violent crimes. Non-violent crimes were dispersed equally among ethnic groups whereas schizophrenia and violence were together and crimes of violence came to the forefront among immigrants and their children (2).…”
mentioning
confidence: 99%